Continuing training spaces for the teaching of written language - Arandia Rodríguez, Sandra Cecilia; Díaz Chaves, Sandra Milena (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This article presents the result of the background analysis for the research project Significant spaces in continuing training of in-service teachers regarding practices in the teaching of written language: alternatives from the perspective of Communities of Practice. These spaces highlight the importance of continuing formation models for in-service teachers, their characteristics and specificities. In this respect, particular emphasis is placed on communities of learning and practice, as well as on constructivist, behavioral, and cognitive approaches, in order to visualize the perspectives and conceptions of teachers regarding the teaching of written language. It follows from this research process that it is important to revise such spaces to support transformation of practices in the teaching of written language. Likewise, it is necessary to find those considering contexts, experiences, skills, and knowledge, which can be geared towards the collective construction of knowledge and meaning. Pedagogical work, particularly the teaching of written language, is thus enhanced as a social practice, since it uses students’ previous knowledge and hypotheses as a basis